Voriconazole metabolism is influenced by severe inflammation: a prospective study - Veringa, Anette; Ter Avest, Mendy; Span, Lambert F R; van den Heuvel, Edwin R; Touw, Daan J; Zijlstra, Jan G; Kosterink, Jos G W; van der Werf, Tjip S; Alffenaar, Jan-Willem C (Journal of antimicrobial chemotherapy, 2017)
During an infection or inflammation, several drug-metabolizing enzymes in the liver are down-regulated, including cytochrome P450 iso-enzymes. Since voriconazole is extensively metabolized by cytochrome P450 iso-enzymes, the metabolism of voriconazole can be influenced during inflammation via reduced clearance of the drug, resulting in higher voriconazole trough concentrations. To investigate prospectively the influence of inflammation on voriconazole metabolism and voriconazole trough concentrations. A prospective observational study was performed at the University Medical Center Groningen. Patients were eligible for inclusion if they were ≥18 years old and treated with voriconazole. Voriconazole and voriconazole-N-oxide concentrations were determined in discarded blood samples. To determine the degree of inflammation, C-reactive protein (CRP) concentrations were used. Subsequently, a longitudinal data analysis was performed to assess the effect of inflammation on the metabolic ratio and voriconazole trough concentration. Thirty-four patients were included. In total 489 voriconazole trough concentrations were included in the longitudinal data analysis. This analysis showed that inflammation, reflected by CRP concentrations, significantly influenced the metabolic ratio, voriconazole trough concentration and voriconazole-N-oxide concentration (all P < 0.001), when corrected for other factors that could influence voriconazole metabolism. The metabolic ratio was decreased by 0.99229 and the voriconazole-N-oxide concentration by 0.99775 , while the voriconazole trough concentration was increased by 1.005321 , where N is the difference in CRP units (in mg/L). This study shows that voriconazole metabolism is decreased during inflammation, resulting in higher voriconazole trough concentrations. Therefore, frequent monitoring of voriconazole serum concentrations is recommended during and following severe inflammation.